Rain, temperature and agricultural production: The impact of climate change in Sub-Sahara Africa, 1961-2009 - Andreas Exenberger; Andreas Pondorfer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
This paper is about the effect of climate change on Sub-Sahara African (SSA) agricultural production in a post-colonial setting. While agricultural production certainly is the result of a multi-dimensional process (influenced by diverse branches of politics, by technology, and also by trade patters and violent conflicts, among others), already the partial analysis of the most obvious factors of influence is certainly valuable in the African case. Since agriculture is not only the single most important sector for the greatest majority of people there, but also a low-tech endeavor in Africa, the impact of temperature and particularly rainfall is crucial - to the point of life-threatening crop failure. In sum, we are able to shown that climate change influenced agricultural production in Sub-Sahara Africa in an unfavourable way. When considering traditional and modern inputs (labour, land and livestock, as well as capital and fertilizer, respectively) in a fixed-effects-model, particularly the effect of rainfall is significantly positive and important. Further, by separating countries into a low- and a med-tech group (with respect to modern inputs), different relationships between the standard factors can be revealed, and by refining the specification with respect to regional climatic differences some complexities in these general patterns can be shown.
Keywords: N57; O13; Q54; 330; Sub-Sahara Africa; agriculture; climate change; panel regression; Klimaveränderung; Agrarproduktion; Afrika südlich der Sahara